THE MODERATING EFFECT OF AGE, INCOME, GENDER, EXPERTISE, LOYALTY PROGRAM, AND CRITICAL INCIDENT ON THE INFLUENCE OF CUSTOMER SATISFACTION TOWARDS CUSTOMER LOYALTY IN AIRLINE INDUSTRY: A CASE OF PT. X - Dionisius Kenny Sugianto (iBuss Management, 2017)
Customer loyalty has been the end purpose for every company. Researchers have acknowledged that a loyal customer always comes from a satisfied customer. Many companies and researchers alike find satisfied customer still abandon and switch to others. This encourages the notion that satisfaction and loyalty is not straight forward. This research shows how the relationship between satisfaction and loyalty has advanced into a stage that requires reexamination of moderating variables. The purpose of the research is to present empirical evidence of variables in which the satisfaction and loyalty relationship becomes stronger or weaker particularly in service sector in Indonesia. Using a sample of 125 customers of airline industry (PT. X) and Moderated Regression Analysis, the researcher examine moderating activity of 6 variables which includes (1) age, (2) income, (3) gender, (4) expertise, (5) loyalty program and (6) critical incident. The results suggest not all variable moderates the relationship. Age, income, expertise and critical Incident are relevant moderators while loyalty program and gender are not. Keywords: Customer Loyalty, Customer Satisfaction, Moderating, Service, Airline, Indonesia